2013
DOI: 10.1590/s0100-29452013000400020
|View full text |Cite
|
Sign up to set email alerts
|

Intensidades da poda seca e do desbaste de cacho na composição da uva Cabernet Sauvignon

Abstract: PRUNING AND CLUSTER THINNING INTENSITY ON THE COMPOSITION OF CABERNET SAUVIGNON GRAPEABSTRACT -The research was carried out in a Cabernet Sauvignon (Vitis vinifera L.) vineyard during four years in Bento Gonçalves-RS, Brazil. The objective was to determine the effect of the pruning and thinning intensity on the variables related to the grapevine yield components and grape must composition. Treatments consisted of two levels of pruning -short and long -and four levels of thinning (%) -0, 25, 50 and 75 -; there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
2
9
0
4
Order By: Relevance
“…Results similar to those observed for 'Thompson Seedless' grapevine were reported in different cultivars, highlighting an inverse relationship between number of bunches per plant and SS (EZZAHOUANI; WILLIAMS, 2003;KUNIHISA et al, 2003;KAVOOSI et al, 2009;SOMKUWAR ;RAMTEKE, 2010;BERKEY et al, 2011;PASTORE et al, 2011;MIELE;RIZZON, 2013). Dayer et al (2013) suggested, from a study with the 'Malbec' grapevine, that bunch thinning has a greater impact on the ratio between simple and reserve sugars (starch) than the total content available in the plant.…”
Section: Resultssupporting
confidence: 71%
“…Results similar to those observed for 'Thompson Seedless' grapevine were reported in different cultivars, highlighting an inverse relationship between number of bunches per plant and SS (EZZAHOUANI; WILLIAMS, 2003;KUNIHISA et al, 2003;KAVOOSI et al, 2009;SOMKUWAR ;RAMTEKE, 2010;BERKEY et al, 2011;PASTORE et al, 2011;MIELE;RIZZON, 2013). Dayer et al (2013) suggested, from a study with the 'Malbec' grapevine, that bunch thinning has a greater impact on the ratio between simple and reserve sugars (starch) than the total content available in the plant.…”
Section: Resultssupporting
confidence: 71%
“…The results of this study were probably due to a variety of factors, such as the source/sink relationship during the grape-ripening period, where the crop load might have played a role. However, an experiment carried out over four years under the same soil conditions comparing two pruning intensities and four thinning intensities showed that, on average, total soluble solids increased by only 0.47 °Brix whereas the yield per hectare decreased from 32.82 t ha -1 to 10.97 t ha -1 (MIELE; RIZZON, 2013). This data supports the idea that crop loadings may have had little effect on the differences found between treatments and it should also be mentioned that the climatic conditions, soil physicochemical characteristics and vineyard management were similar to those of the present experiment.…”
Section: Resultsmentioning
confidence: 99%
“…There are many works relating yield and total soluble solids in grapes. Some show that there is no direct relationship between them [12] and others found that the increase of sugar in grape is proportionally low compared to the reduction of productivity [13]. But, most works show that the higher the yield, the lower the sugar concentration in grape berries [14].…”
Section: Resultsmentioning
confidence: 99%